Determinants of organisational blockchain usage behaviour within the South African financial services industry - Paul, Ashley J. (University of the Witwatersrand, Johannesburg, 2023)
This report presents findings on individual blockchain usage behaviour at the organizational-level in the South African financial services industry. The study examined the influences of perceived usefulness, motivational factors, design and implementation, and perceived ease of use, on blockchain adoption behaviour. Empirical results from quantitative analyses following a survey of technical and non-technical managers within the South African Banking and Financial Service Industry (BFSI) (n = 158) revealed key insights. Perceived usefulness, while important, had a negative effect on blockchain usage behaviour, indicating that managers prioritize other organizational drivers over perceived usefulness. Motivational factors were insignificant, requiring further investigation with aligned respondent profiles. Design and implementation emerged as a highly significant factor, emphasizing the need for well-designed systems, user-friendly interfaces, and integration with existing processes. Perceived ease of use was insignificant, potentially due to managers' assumed background knowledge. The report concluded by highlighting the complexities and challenges of blockchain adoption in the South African financial services industry and recommended comprehensive education and training, well-designed implementations, and assessment of unique adoption factors. The study contributed to the existing literature by focusing on organisational-level blockchain usage behaviour and extending the Technology Acceptance Model (TAM). Future research must involve the examination of digital maturity, delivery methodologies, and the impact of non-technical skills on blockchain adoption behaviour. Overall, the study provides valuable insights for practitioners and researchers seeking to enhance blockchain adoption in organizational contexts
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of digital business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Blockchain; Adoption Factors; Banking and Financial Services Industry (BFSI); Individual Usage Behaviour at the Organisational Level; South Africa; UCTD; SDG-8: Decent work and economic growth